Centredness in health care: A systematic overview of reviews. (8th March 2022) - Feldthusen, Caroline; Forsgren, Emma; Wallström, Sara; Andersson, Viktor; Löfqvist, Noah; Sawatzky, Richard; Öhlén, Joakim; J. Ung, Eva
Abstract: Introduction: The introduction of effective, evidence‐based approaches to centredness in health care is hindered by the fact that research results are not easily accessible. This is partly due to the large volume of publications available and because the field is closely linked to and in some ways encompasses adjoining fields of research, for example, shared decision making and narrative medicine. In an attempt to survey the field of centredness in health care, a systematic overview of reviews was conducted with the purpose of illuminating how centredness in health care is presented in current reviews. Methods: Searches for relevant reviews were conducted in the databases PubMed, Scopus, Cinahl, PsychINFO, Web of Science and EMBASE using terms connected to centredness in health care. Filters specific to review studies of all types and for inclusion of only English language results as well as a time frame of January 2017–December 2018, were applied. Results: The search strategy identified 3697 unique reviews, of which 31 were included in the study. The synthesis of the results from the 31 reviews identified three interrelated main themes: Attributes of centredness (what centredness is), Translation from theory into practice (how centredness is done) and Evaluation of effects (possible ways of measuring effects of centredness). Three main attributes of centeredness found were: being unique, being heard and shared responsibility. Aspects involved in translating theory into practice were sufficient prerequisites, strategies for action and tools used in safeguarding practice. Further, a variety and breadth of measures of effects were found in the included reviews. Conclusions: Our synthesis demonstrates that current synthesized research literature on centredness in health care is broad, as it focuses both on explorations of the conceptual basis and the practice, as well as measures of effects. This study provides an understanding of the commonalities identified in the reviews on centredness in healthcare overall, ranging from theory to practice and from practice to evaluation. Patient or Public Contribution: Patient representatives were involved during the initiation of the project and in decisions about its focus, although no patient or public representatives made direct contributions to the review process.